A model for assessing blog-based learning systems success. Issue 7 (4th November 2014) - Wang, Yi-Shun; Li, Hsien-Ta; Li, Ci-Rong; Wang, Chian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Based on previous information systems/educational technology success models, the purpose of this paper is to establish a comprehensive, multidimensional model for assessing blog-based learning systems success. Design/methodology/approach – Data collected from 240 blog-based learning systems users in the context of higher education were tested against the model using the structural equation modelling approach. Findings – The results indicate the interrelationships between six system success variables: system quality, content quality, context and linkage quality, user satisfaction, system use, and learning performance. In particular, this study confirms that quality attributes positively affect user satisfaction, which in turn positively influences learning performance directly or indirectly through the mediation of system use. Originality/value – This study is a pioneering effort to develop and validate a blog-based learning systems success model.